Peningkatan Kualitas Loloh Beluntas di Desa Saba Kecamatan Blahbatuh Kabupaten Gianyar - Putu Lakustini Cahyaningrum; Sang Ayu Made Yuliari; Anak Agung Ayu Sauca Sunia Widyantari; Putut Dewantha Jenar; Made Kresna Aditama Duarba; Gusti Ayu Linda (JURNAL SEWAKA BHAKTI, 2022)
Loloh beluntas is one of the traditional Balinese drinks that have properties to maintain body fitness and health. Efforts to improve the quality of the traditional Balinese drink, namely loloh beluntas, need to be carried out in order to obtain adequate and hygienic results so that they can enter the market share. In this PKM there is a partner, namely Mrs. Ketut Murniati who produces loloh beluntas every day to be marketed in Saba Village, Blahbatuh District, Gianyar Regency. At this time, there are some constraints of partners namely: lack of knowledge and skills in the processing of loose beluntas from scratch making raw materials to manufacture loose beluntas that hygenis (tools that are still manual), yet well preserved making it less able to compete with otherproducts loloh. Lack of knowledge about properpackaging and labeling techniques loloh to produce more attractive products and do not yet have a product identity. Lack of storage space for loloh beluntas that affects production and selling value. Based on the problems faced, it is necessary to carry out an activity to foster and assist partners so that they can improve the welfare of partners. The activity begins with socialization, providing tools to improve production quality, providing assistance in processing loloh and developing loloh beluntas packaging designs. Indicators of achievement are an increase in the knowledge and skills of partners in the processing of loloh beluntas, an increase in the amount of production and an increase in the amount of income.